PERAN KEPEMIMPINAN DALAM UPAYA MENINGKATKAN KUALITAS KERJA, DIDUKUNG DENGAN PENGUATAN SEMANGAT KERJA - Sugiarti, Endang (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
Quality of work is one of the main instruments that show the achievement of performance. For companies, performance is a necessity, which must be realized, as evidence of achieving goals. Therefore, it takes the involvement of all parties, especially the leadership. Leaders have an important role in influencing and inviting all employees to work totally in realizing company goals. In addition, the inherent optimism and enthusiasm is a supporting factor for improving performance. In this regard, this study aims to analyze and explain the possible influence of leadership and work motivation on improving performance. Methodologically, this research is quantitative based using multiple linear regression statistics. In collecting data, a questionnaire method was used, so that the answer scale was obtained. The results showed that the partial and simultaneous statistical results were in the significant category. That is, a good leader can encourage the creation of a productive work environment, an environment that breeds enthusiasm for work, and has a strong desire to give the best results. Likewise, work motivation has a real influence on the psychological state of employees, namely a self-motivation to be able to contribute to the interests of the company.